2019
DOI: 10.3389/fsufs.2019.00005
|View full text |Cite
|
Sign up to set email alerts
|

Climate Impacts of Cultured Meat and Beef Cattle

Abstract: Improved greenhouse gas (GHG) emission efficiency of production has been proposed as one of the biggest potential advantages of cultured meat over conventional livestock production systems. Comparisons with beef are typically highlighted, as it is a highly emissions intensive food product. In this study we present a more rigorous comparison of the potential climate impacts of cultured meat and cattle production than has previously been made. Warming impacts are evaluated using a simple climate model that simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(143 citation statements)
references
References 31 publications
3
138
0
2
Order By: Relevance
“…In particular, scientists in academia and industry are working to further the development of cultured meat, which can be grown from animal cells rather than by rearing animals [78]. Cultured meat production does not need to harm animals and potentially has a lower environmental footprint than conventional meat [79]. Therefore, producing meat in this way could allow consumers to continue enjoying the taste and texture of animal meat whilst circumventing many of the ethical and environmental concerns around meat production.…”
Section: Addressing Objections Through Animal Product Alternativesmentioning
confidence: 99%
“…In particular, scientists in academia and industry are working to further the development of cultured meat, which can be grown from animal cells rather than by rearing animals [78]. Cultured meat production does not need to harm animals and potentially has a lower environmental footprint than conventional meat [79]. Therefore, producing meat in this way could allow consumers to continue enjoying the taste and texture of animal meat whilst circumventing many of the ethical and environmental concerns around meat production.…”
Section: Addressing Objections Through Animal Product Alternativesmentioning
confidence: 99%
“…Furthermore, these materials have been modified, either as microspheres or bulk, to possess the porosity necessary for diffusion of nutrients through dynamic or static bioreactors (Oh et al, 2009;Wu et al, 2011;García Cruz et al, 2012;Varley et al, 2017;Huang et al, 2018;Specht et al, 2018). In order to scale an animal-free product with similarities to that of native animal tissue, the need for fetal bovine serum, costeffective engineering processes, antibiotic dependence, scaffold development, and cell line(immortalized vs. primary and cell co-culture) needs to be addressed (Specht et al, 2018;Stephens et al, 2018;Lynch and Pierrehumbert, 2019). It's currently believed that scaffolding will play a crucial role in the scalability of cultured meat.…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, the production of cultured meat is presented as environmentally friendly, because it is supposed to produce less GHG (which is a matter of controversy), consume less water and use less land (this point being obvious) in comparison to conventional meat production (13,24,25), from ruminants particularly. However, this type of comparison is incomplete and sometimes biased or at least, partial as discussed below.…”
Section: Comparison Of Environmental Impact With Conventional Farmingmentioning
confidence: 99%
“…In a recent study, Lynch et al (24) concluded that global warming will be less with cultured meat than with cattle initially, but not in the long term because CH 4 does not accumulate as so long in the atmosphere unlike CO 2 . In some cases, cattle systems are characterized by a greater peak warming compared to in vitro meat.…”
Section: Comparison Of Environmental Impact With Conventional Farmingmentioning
confidence: 99%